1996
DOI: 10.1111/j.1479-828x.1996.tb02180.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Meconium‐Aspiration Syndrome

Abstract: The aim of this retrospective study was to identify risk factors for meconium-aspiration syndrome, and to identify antenatal and intrapartum risk factors which might be preventable. We analyzed maternal and neonatal records of the 210 infants who had meconium-stained liquor and who also developed respiratory distress necessitating admission to the Special Care of Intensive Care Baby Units at National Women's Hospital, Auckland in 1992. Meconium-aspiration syndrome occurred in 6.6% of meconium exposed babies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 13 publications
2
23
0
2
Order By: Relevance
“…Urbaniak et al 8 objetivaram identificar fatores de risco para a SAM nos períodos antenatal e intraparto que pudessem ser prevenidos; para tal, analisaram 210 neonatos que apresentaram mecônio no líquido amniótico e que desenvolveram distúrbios respiratórios no pós-parto imediato. A incidência de SAM foi de 6,6% em crianças expostas ao mecônio, e de 1,3% na população geral de nascimentos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Urbaniak et al 8 objetivaram identificar fatores de risco para a SAM nos períodos antenatal e intraparto que pudessem ser prevenidos; para tal, analisaram 210 neonatos que apresentaram mecônio no líquido amniótico e que desenvolveram distúrbios respiratórios no pós-parto imediato. A incidência de SAM foi de 6,6% em crianças expostas ao mecônio, e de 1,3% na população geral de nascimentos.…”
Section: Discussionunclassified
“…Urbaniak et al (1996) 8 encontraram associação significante entre a SAM e a primiparidade. Usta et al (1995) 10 relataram que o tabagismo esteve relacionado com riscos mais baixos de SAM.…”
Section: Discussionunclassified
“…Those factors are heavy MSAF, nulliparity, postterm delivery, fetal heart rate (FHR) abnormalities during labor, presence of meconium below the vocal cords, cesarean delivery and the low Apgar scores. 13,14,20,[25][26][27][28][29][30] It has been reported that there is an apparent relationship between maternal ethnicity and risk of MSAF, and the risk of MAS having been observed to be increased in black Americans, Africans and Pacific Islanders. [30][31][32] Intrapartum fetal monitoring The goal of continuous electronic fetal heart rate monitoring (EFM) is to detect fetal hypoxemia and therefore reduce the risk of adverse neonatal outcomes.…”
Section: Pathophysiology and Risk Factorsmentioning
confidence: 99%
“…1,[12][13][14] The case fatality rate of MAS has been reported to be high, ranging from 5 to 40%. 1,[13][14][15][16][17] Approximately one-third of babies with MAS require intubation and mechanical ventilation, and other new therapies such as high frequency ventilation, inhaled nitric oxide and surfactant administration, although the effectiveness of certain of these technologies remain controversial. 2,[17][18][19] Serious complications resulting from MAS include pneumothorax, convulsion and death.…”
Section: Introductionmentioning
confidence: 99%
“…MAS has been reported to occur in 6.6-30% of cases complicated with MSAF and in 1-3% of liveborn infants. [7][8][9] The case fatality rate of MAS has been reported to be high, ranging from 5 to 40%. 8,[10][11][12] Amnioinfusion (AI), or transcervical infusion of saline into the amniotic cavity, has been proposed as a method to reduce MAS.…”
Section: Introductionmentioning
confidence: 99%